Penerapan Komunikasi Interpersonal Tenaga Pendidik dalam Pencapaian Prestasi Belajar Siswa di MTs Nahdliyatul Islamiyah Blumbungan Larangan Pamekasan - Nurhadi, Ali; Niswah, Fitrotun (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2019)
Communication is the process of interaction carried out by someone both directly and indirectly in everyday life. Interpersonal communication is the process of delivering messages between two people or small groups directly, both verbal and nonverbal messages, with the aim of achieving similar meaning. Interpersonal communication for teachers is important for student achievement. Therefore the research was carried out with the title: Application of Interpersonal Communication of Educators in Achieving Student Learning Achievement at Nahdliyatul Islamiyah Blumbungan MTs. This study uses a qualitative approach to the type of phenomenology. Data sources were obtained through interviews, observation and documentation. His informants were the principal, the teachers. While checking the validity of the data is done through source tringulation. The results showed that: first, in the application of educator interpersonal communication is (1) cooperation between school members is very important, (2) feedback that occurs in interpersonal communication there is a positive response, (3) while the obstacles that occur in interpersonal communication are the presence of teachers to the madrasa so that teachers feel less time in communicating. Second, effective interpersonal communication for educators is (1) a teacher must have openness in interpersonal communication, (2) empathy in effective interpersonal communication also influences the process of interaction in madrasas because with empathy we can feel what people feel other.